Overview of Outpatient Patient Prescription Completeness in Pharmacy Installation o f General Hospital Indonesia Christian University - Lumbantobing, Romauli; Hendrika, Wendy; Pradnyanata, Made Gandeva (CV. AFDIFAL MAJU BERKAH, 2025)
Medication errors are preventable and endangering events that still occur when patients receive treatment from healthcare professionals. One form of such error is incomplete prescriptions, which can have a negative impact on the effectiveness of therapy and patient safety. This phenomenon is commonly found in various healthcare facilities in Indonesia. Methods: This study aims to determine the completeness of outpatient prescriptions at the Pharmacy Installation of the Indonesian Christian University General Hospital (RSU UKI), especially from the administrative and pharmaceutical aspects. This study is a non-experimental retrospective descriptive study with a quantitative approach. Samples were taken randomly directly from outpatient prescriptions that entered the UKI Hospital Pharmacy Installation during the period October to December 2022. Results: From the evaluation results of the prescriptions studied, data was obtained that the level of completeness in the administrative aspect included: pro (patient and doctor identity) of 73.80%, inscriptio (health care facility identity) 92.85%, invocatio (symbol R/) 100%, and subscriptio (technical instructions for pharmacists) 79.77%. Meanwhile, in the pharmaceutical aspect, the level of completeness of the signatura (instructions for use for patients) reached 91.67% and prescriptio (medicine name, dosage, dosage form, and quantity) was 88.39%. Conclusion: The results of the study indicate that most outpatient prescriptions at the Pharmacy Installation of RSU UKI have met the standards of administrative and pharmaceutical completeness. However, there are still shortcomings in several components, especially in the pro and subscriptio sections. Efforts are needed to improve accuracy in writing prescriptions by medical personnel to minimize the risk of medication errors and improve patient safety.